How should the Army use contractors on the battlefield? : assessing comparative risk in sourcing decisions - Camm, Frank A., 1949-; Greenfield, Victoria A., 1964-; Arroyo Center. Manpower and Training Program; Rand Corporation; United States. Army. (Santa Monica, CA : RAND, 2005)
Can the Army improve the way it measures the risks of using civilian contractors in combat? This report proposes a method for comparing the "residual risks" of using military and contract sources to perform specific support activities on the battlefield. It applies the Army's standard approach to risk assessment, which identifies sources of risk, or "threat"; the risks the threats present; the opportunities to mitigate these risks; and the risk that remains-the residual risk-when the Army chooses a particular course of action to mitigate risks. The approach considers choices of military and contract sources, with appropriate mitigation strategies, as alternative courses of action and compares the residual risks associated with each choice. The approach offers an orderly way to translate relative inherent capabilities of military and contract sources, terms of applicable status-of-forces agreements, and threats at any particular place and time on the battlefield into a comparison of the residual risks associated with military outcomes, the safety of contract personnel, resource costs, and other policy factors of greatest importance outside a particular contingency setting.
"RAND Arroyo Center."
Includes bibliographical references (p. 203-216).
Also available on the internet via WWW in PDF format.
Keywords: United States. -- Army -- Appropriations and expenditures; United States. -- Army -- Supplies and stores; Civil-military relations -- United States; Combatants and noncombatants (International law); Contracting out -- United States -- Decision making; Defense contracts -- United States; Logistics -- Contracting out -- United States; Operational readiness (Military science)